Utilizing Artificial Intelligence to Design Adaptive Learning Systems Aligned with the 2024 Curriculum - Abizar Tri Pangestu (Institute of Accounting Research and Novation (IARN), 2024)
This research explores the application of Artificial Intelligence (AI) in designing adaptive learning systems aligned with the 2024 curriculum goals. The study investigates how AI technologies, including neural networks, decision trees, and Bayesian networks, can personalize learning paths to meet the diverse needs of students. By analyzing recent developments and implementing AI-driven adaptive platforms in real classroom settings, the research examines the impact of personalized learning on student engagement, academic performance, and inclusivity. Results show that AI significantly enhances the alignment between instructional content and individual learner profiles, supports timely teacher interventions through real-time analytics, and promotes more equitable learning opportunities. Compared to previous studies, this research extends the understanding of AI’s role by focusing on a broader set of competencies beyond subject-specific knowledge, such as critical thinking and digital literacy. The findings conclude that AI-powered adaptive learning, when integrated thoughtfully and supported by effective teacher training, holds substantial promise for transforming education into a more flexible, efficient, and student-centered process.